The Malay language a bridge to knowledge - Chew, Fong Peng (Culture, language and literature in Malaysian society)
The books present the view of Malaysian scholar of Chinese descent on the national culture, language, and literature as seen from her perspective, distinctly different from that of Malay writers in their own realm.